PENINGKATAN PENGETAHUAN TENTANG TRIPLE ELIMINATION DI PIJOAN, MUARO JAMBI - Herlambang Herlambang; Erny Kusdiyah; Ahmad Syauqy; Asro Hayani Harahap (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2021)
ABSTRACT Background HIV, syphilis, and hepatitis B infections in children are more than 90% infected from their mothers. The risk of mother-to-child transmission for HIV is 20%-45%, for syphilis is 69-80%, and for hepatitis B it is more than 90%. Intervention needs to be made to break the chain of transmission of HIV, Syphilis, and Hepatitis B through the Elimination programme. The aim was to enhance knowledge about Triple Elimination. Methods workshop with the theme of triple elimination on pregnant women in Pijoan was performed. Pretest and posttest questions were given to measure knowledge about triple elimination in pregnant women. The result of this programme was an increase in the knowledge shown by the number of correct answers during the pretest was more compared to the post-test. Keywords Triple Elimination, Hepatitis B, HIV, Syphilis ABSTRAK Latar belakang Infeksi HIV, Sifilis, dan Hepatitis B pada anak lebih dari 90% tertular dari ibunya. Risiko penularan dari ibu ke anak untuk HIV adalah 20%-45%, untuk Sifilis adalah 69-80%, dan untuk Hepatitis B adalah lebih dari 90%. Perlu dilakukan upaya untuk memutus rantai penularan HIV, Sifilis, dan Hepatitis B melalui Eliminasi Penularan. Upaya Eliminasi Penularan HIV. Tujuan meningkatkan pengetahuan Tentang Triple Elimination. Metode Kegiatan diawali oleh workshop bertema triple elimination pada ibu hamil di Pijoan. Diberikan soal pretest dan post test untuk mengukur pengetahuan tentang triple elimination pada ibu hamil. Hasil terdapat peningkatan jumlah benar saat pretest dibandingkan post test. Kata Kunci: Triple Elimination, Hepatitis B, HIV, Sifilis